Dip-pen nanolithography-generated patterns used as gold etch resists : a comparison study of 16-mercaptohexadecanioc acid and 1-octadecanethiol - Lu, Gang (2012)
The etch resist ability of dip-pen nanolithography (DPN)-generated dot patterns of different alkanethiols on Au was systematically studied. After 16-mercaptohexadecanioc acid (MHA) and 1-octadecanethiol (ODT) dots with different diameters were patterned on a Au substrate by DPN, the substrate was etched in a feri-/ferrocyanide solution. Tapping mode AFM (TMAFM) was used to monitor the morphology change of the patterned dots during the wet chemical etching. The diameter and height of MHA and ODT dots at different etch time were measured by TMAFM. The resist ability of the patterned MHA and ODT SAMs on Au was compared. The result shows that the MHA patterns have better etch resist ability than do ODT patterns.